Family Education Factors and Their Influence on Entrepreneurial Potential: Systematic Literature Review - Kurniawan, Bonifatius Aditya; Guritno, Bernardus Singgih (SMARTINDO, 2024)
Purpose - This research aims to conduct a systematic literature review on the factors of family education and their impact on entrepreneurial potential development. Family education is one of the important factors in shaping someone's entrepreneurial attitudes, skills, and interests. In this context, the research aims to reassemble existing information from various previous studies related to family education factors and entrepreneurial development. Design/methodology/approach - The method used in this research is a systematic literature review. Data were obtained from relevant sources such as academic journals related to family education and entrepreneurship from the years 2020 to 2023. The collected data were then analyzed and organized to identify family education factors that influence entrepreneurial development, as well as their impact on motivation, attitudes, skills, and entrepreneurial success. Findings and Discussion - The results of this systematic literature review indicate that family education plays a significant role in shaping individuals' entrepreneurial attitudes. Factors such as parental influence, family environment, values, and habits applied within the family can influence someone's interest and motivation to become an entrepreneur. This research provides valuable insights into the importance of family education in shaping entrepreneurship. The implications of this research are the need for greater attention to the role of the family in supporting entrepreneurial development, both through family education programs and relevant policy support. By understanding the family education factors that influence entrepreneurship, steps can be taken to enhance interest and success in entrepreneurship within society. Conclusion - The Family has a significant influence on entrepreneurial interest and development.